Monitoring of Pathogens Carried by Imported Flies and Cockroaches at Shenzhen Ports - Siqi Zhang; Chunzhong Zhao; Guoping Liu; Liwei Guo; Ran Zhang; Junyu Yan; Jianan He; Cheng Guo (Tropical Medicine and Infectious Disease)
This study tested the efficacy of xenomonitoring using contaminated flies and cockroaches at ports in Shenzhen by analysing sample data from imported flies and cockroaches from October 2023 to April 2024 to identify the pathogens they carried. Among all the samples of flies and cockroaches collected, Musca domestica vicina and Blattella germanica accounted for the highest proportion, 27.59% and 66.47%, respectively. Their positive rates for carrying Staphylococcus aureus were also the most significant, reaching 4.35% and 6.47%, respectively. The imported flies and cockroaches mainly came from Asia, with the highest proportion coming from Hong Kong, at 97.71% and 92.11%, respectively. Metagenomic sequencing indicated that the pathogens carried by the flies and cockroaches from different regions of Asia were generally similar but showed some differences. Flies from Southeast Asia, East Asia, South Asia, and West Asia and cockroaches from Southeast Asia, East Asia, and West Asia harboured unique opportunistic pathogens capable of causing gastrointestinal and respiratory infections in humans. Specifically, flies carried pathogens such as Campylobacter jejuni, Bacillus anthracis, Bacteroides fragilis, and Bordetella bronchiseptica, while cockroaches carried B. fragilis, Clostridium tetani, and Bacillus cereus. Our findings provide data support for future risk assessments of pathogens carried by imported vectors.